Simple AR Basketball For Android Devices - Nur Hadisukmana; Dias Teddo Wicaksono (IT for Society, 2018)
These days many people doing a lot of activities. Entertainment is one solution to reduce stress from those activities. Game is one of entertainment type, most of people playing games every day. People in these days using their smartphone to do a lot of things, smartphone becomes most important thing for people handles their life, people bring it every day and everywhere. Now, many game developer develop game on smartphone, most of them develop the 2D game or 3D game. This research will develop an casual game application on android device, combine 3D environment and Augmented Reality (AR) environment.